Calpain is a mediator of preservation-reperfusion injury in rat liver transplantation - Kohli, Vivek (The National Academy of Sciences of the USA, 1997)
Proteases as well as alterations in intracellular calcium have important roles in hepatic preservation-reperfusion injury, and increased calpain activity recently has been demonstrated in liver allografts. Experiments were designed to evaluate (i) hepatic cytosolic calpain activity during different periods of cold ischemia (CI), rewarming, or reperfusion, and (ii) effects of inhibition of calpain on liver graft function using the isolated perfused rat liver and arterialized orthotopic liver transplantation models. Calpain activity was assayed using the fluorogenic substrate Suc-Leu-Leu-Val-Tyr-7-amino-4-methyl coumarin (AMC) and expressed as mean ± SD pmol AMC released/min per mg of cytosolic protein. Calpain activity rose significantly after 24 hr of CI in University of Wisconsin solution and further increased with longer preservation. Activity also increased within 30 min of rewarming, peaking at 120 min. Increased durations of CI preceding rewarming resulted in significantly higher activity (P < 0.01). Calpain activity increased rapidly upon reperfusion and was significantly enhanced by previous CI (P < 0.01). Calpain inhibition with Cbz-Val-Phe methyl ester significantly decreased aspartate aminotransferase released in the isolated perfused rat liver perfusate (P < 0.05). Duration of survival after orthotopic liver transplantation using livers cold-preserved for 40 hr was also significantly increased (P < 0.05) with calpain inhibitor. In conclusion, calpain proteases are activated during each phase of transplantation and are likely to play an important role in the mechanisms of preservation-reperfusion injury.